The Japanese marketing system : adaptations and innovations - Yoshino, M. Y. (Cambridge : MIT Press, 1971)
It focused on the dynamic economic and social development in contemporary Japan.
Includes bibliography and index
kjo 18/01/2019
Loans
Keywords: Marketing